2015
DOI: 10.1111/1541-4329.12056
|View full text |Cite
|
Sign up to set email alerts
|

A View of Oral Communication Activities in Food Science From the Perspective of a Communication Researcher

Abstract: Food science researchers have pronounced the Institute of Food Technologists Success Skills to be the most important competency mastered by graduates entering the work force. Much of the content and outcomes of the Success Skills pertains to oral communication skills of public speaking and interpersonal and group communication. This qualitative study reports the results of an examination of oral communication activities in the classes of 9 faculty in the food science program at Iowa State Univ. The findings re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2015
2015
2016
2016

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 18 publications
0
4
0
Order By: Relevance
“…The present investigation was conducted in the Department of Food Science and Human Nutrition at a Midwestern research university. The study is part of a larger study in which I examined the connection of oral communication traditions and the food science discipline (for other results of the study, see Vrchota, 2011;2015a;2015b).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The present investigation was conducted in the Department of Food Science and Human Nutrition at a Midwestern research university. The study is part of a larger study in which I examined the connection of oral communication traditions and the food science discipline (for other results of the study, see Vrchota, 2011;2015a;2015b).…”
Section: Methodsmentioning
confidence: 99%
“…The experiences of four decades have resulted in a tradition in the communication discipline that guides in integration efforts with other disciplines (see, for example, Cronin & Grice, 1993;Cronin, Grice, & Palmerton, 2000;Dannels, 2001: Dannels & Housley Gaffney, 2009Morreale, Shockley-Zalabak & Whitney, 1993;Steinfatt, 1986;Strohmeier, Novak, Stratton, & Leipzig, 1992;and Weiss, 1990). To date, studies of communication integrations are available for the disciplines of engineering (Dannels, 2002(Dannels, , 2003Dannels, Anson, Bullard, & Peretti, 2003;Darling, 2005;Darling & Dannels, 2003), design (Dannels, 2005;Dannels, Gaffney, & Martin, 2008;Dannels & Norris Martin, 2008;Housley Gaffney, 2015;Morton, 2006;Morton & O'Brien, 2005), public education (Smith, 2005), dietetics (Vrchota, 2011) and food science (Reitmeier & Vrchota, 2009;Vrchota, 2015a;Vrchota, 2015b).…”
Section: Tradition Of Communication Integrationsmentioning
confidence: 99%
“…As an example, 9 food science faculty members at Iowa State Univ. developed curricula that involved communication activities to support the IFT communication success skill (Vrchota ). A qualitative survey of the oral communication activities in the classes of the 9 faculty members revealed that the students received no explicit teaching regarding oral communication in such classes and that the faculty members assumed that the desired proficiencies in oral communications would be attained through student participation in oral communication class activities (Vrchota ).…”
Section: Introductionmentioning
confidence: 99%
“…It is my opinion that such best practices are portable to other groups of learners, including undergraduate students, postdoctoral scholars, faculty members, and food science professionals in industrial, consulting, and government settings. Incorporation of these best practices in the oral communication training of undergraduate food science students can alleviate the disconnect identified by Vrchota () where students were required to frequently engage in oral communication classroom activities but did not receive formal oral communication training.…”
Section: Introductionmentioning
confidence: 99%